Development of a Cannabis Assessment Tool (CAT-1) to measure current and lifetime marijuana use among older Veterans. Issue 1 (14th January 2020) - Keyhani, Salomeh; Abraham, Ann; Cohen, Beth; Vali, Marzieh; Yoo, Sodahm Robin; Dollinger, Camille; Steigerwald, Stacey
Abstract : Objective: To develop a tool to assess current (past 30 days) and lifetime marijuana use in older Veterans. Setting: US Veteran's Affairs Healthcare System. Participants: 704 older Veterans were screened, 339 completed the initial survey, 100 completed the follow-up. Primary outcome measure: Pearson's correlation coefficient to assess strength of association between initial and follow-up survey on measures of current and lifetime marijuana use. Results: Both a 'gram-month' measure of marijuana smoked in the past 30 days (r=0.83) and a frequency-based measure assessing total number of times smoked in the past 30 days were reliable (r=0.89). Both a simple categorical measure of lifetime use (agreement=85%) and a continuous measure of lifetime use (r=0.82) were reliable. Conclusions: The Cannabis Assessment Tool offers a reliable assessment of past 30 days and lifetime assessments of smoking cannabis in older adults.